2006
DOI: 10.1007/s00467-006-0224-1
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin decreases furosemide-induced natriuresis and diuresis on the neonatal kidney

Abstract: Indomethacin is used to pharmacologically occlude patent ductus arteriosus in preterm infants. It induces renal untoward effects and furosemide is administered simultaneously to counteract them. The effect of furosemide is blunted by indomethacin. We analyzed comparatively the interactions of furosemide and indomethacin at the organic anion transport system in adult and newborn individuals. Adult and 5-day-old Wistar rats were allocated into three groups: (1) indomethacin (10 mg/kg, ip); (2) furosemide (2 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In human adults, decrease in diuretic response is reported when furosemide is simultaneously administered with indomethacin (17). Animal studies show that indomethacin blunts the natriuretic and diuretic response to furosemide, possibly by blocking the renal vasodilatation associated to the local production of prostaglandins (18) or by interacting at the secretory level of the proximal tubulus (19). In the neonatal kidney, urine output was not different between experiments of indomethacin and indomethacin plus furosemide administration, respectively (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human adults, decrease in diuretic response is reported when furosemide is simultaneously administered with indomethacin (17). Animal studies show that indomethacin blunts the natriuretic and diuretic response to furosemide, possibly by blocking the renal vasodilatation associated to the local production of prostaglandins (18) or by interacting at the secretory level of the proximal tubulus (19). In the neonatal kidney, urine output was not different between experiments of indomethacin and indomethacin plus furosemide administration, respectively (19).…”
Section: Discussionmentioning
confidence: 99%
“…As the subjects of our study are born after a shorter gestation (mean gestational age, 28 weeks) and received earlier postnatal treatment (postnatal age of treatment, 3.7 days) for ductal closure than in the study of Yeh (mean gestational age, 31 weeks; postnatal age of treatment, 9.5 days) and Vargas‐Origel (mean gestational age, 33 weeks; postnatal age of treatment, 6.5 days) maturation might be a determinant (11,12). It has been shown that tubular secretion is reduced by furosemide, indomethacin and furosemide plus indomethacin at 10‐fold lower concentrations in newborn than in adult rats, suggesting that the neonatal kidney is more sensitive than the adult kidney to furosemide–indomethacin interaction (19). In agreement with this are the results of Shaffer et al, who reported higher efficiency of the treatment with furosemide and indomethacin to induce ductal closure in newborns that received early postnatal treatment compared to older (>10 days postnatal) newborns (15).…”
Section: Discussionmentioning
confidence: 99%
“…Indomethacin inhibited the saluretic and diuretic response to furosemide both in adult and newborn rats. Inhibitory interaction between indomethacin and furosemide was achieved at approximately 10-fold lower concentrations in the newborne than in the adult rats, suggesting that the neonate kidney is more sensitive to the action of these drugs than the adult kidney [172]. Indomethacin or meclofenamate blunted the response to furosemide on sodium and chloride transport [173], suggesting that the drugs interact at the Na-K-2Cl cotransporter.…”
Section: Nsaids and Blood Pressurementioning
confidence: 99%
“…3,4 Indomethacin and ibuprofen are pharmacologic agents commonly used to close the hemodynamically significant PDA (hsPDA) in preterm infants. [5][6][7] Surgical ligation is an effective alternative for nonresponders to pharmacologic therapy. 8,9 There has been recent debate about the risk-benefit ratio of treating most infants with PDA 10,11 ; therefore, identifying a biomarker that predicts which infants will become most affected by persistent patency of the DA is of paramount importance.…”
mentioning
confidence: 99%